2018
DOI: 10.1093/toxsci/kfy119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Mechanism(s) That Leads to Platelet Decreases in Cynomolgus Monkeys During Administration of ISIS 104838, a 2ʹ-MOE-Modified Antisense Oligonucleotide

Abstract: ISIS 104838, a 2'-O-methoxyethyl (2'-MOE)-modified antisense oligonucleotide (ASO), causes a moderate, reproducible, dose-dependent, but selflimiting decrease in platelet (PLT) counts in monkeys and humans. To determine the etiology of PLT decrease in cynomolgus monkeys, a 12-week repeat dose toxicology study in 5 cynomolgus monkeys given subcutaneous injections of ISIS 104838 (30-60 mg/kg/week). Monkeys were also injected intravenously with 111Indium(In)-oxine-labeled PLTs to investigate PLT sequestration. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In addition, a heparin‐induced thrombocytopenia‐like mechanism through the induction of anti‐platelet factor 4 IgG antibodies has also been proposed, based on the binding of nucleic acids to platelet factor 4 (Jaax et al, 2013), although contradictory results have been reported. A recent study suggests that sequestration of platelets in the liver and spleen occurs through the activation of monocytes, but not platelets, and is accompanied by increased serum IgM levels (Narayanan et al, 2018). In most cases, thrombocytopenia after treatment with ONs is mild to moderate and reversible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a heparin‐induced thrombocytopenia‐like mechanism through the induction of anti‐platelet factor 4 IgG antibodies has also been proposed, based on the binding of nucleic acids to platelet factor 4 (Jaax et al, 2013), although contradictory results have been reported. A recent study suggests that sequestration of platelets in the liver and spleen occurs through the activation of monocytes, but not platelets, and is accompanied by increased serum IgM levels (Narayanan et al, 2018). In most cases, thrombocytopenia after treatment with ONs is mild to moderate and reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there were no withdrawals due to platelet counts after the company began monitoring the side effect. In contrast, no significant reduction of platelet counts was reported in the COMPASS study [ 15 •, 95 ], and current thinking is that underlying mechanism seems to be linked to the drug delivery methodology and not to apoC-III per se, as another 2′-MOE modified antisense oligonucleotide has been reported to cause dose-dependent reduction of platelets in monkeys and humans [ 107 ]. These potential issues may be addressed by the conjugation of GalNAc to ASO targeting apoC-III which as mentioned above enables liver-specific delivery of the anti-apoC-III ASO and enhanced potency allowing lower doses to be used [ 95 , 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PLT counts between 50,000 and 200,000 cells/µL at doses ≥10 mg/kg/kg was also similar between the GalNAc 3 -MOE ASOs (9.6% to 12.5%) and the unconjugated MOE ASOs (11.5% to 12.2%). This observation indicates that the GalNAc 3 conjugation does not alter the effect of the MOE ASO on PLT counts and argues that the PLT effect is not related to hepatic distribution and is likely a nonspecific effect of the ASO in individual monkeys (Narayanan et al, 2018).…”
Section: Imtd Queriesmentioning
confidence: 81%